Crime, gender, and sexuality in criminal prosecutions - Knafla, Louis A. (Criminal justice history, 2002)
Violence, vendetta, and peacemaking in late medieval Bologna / Trevor Dean -- Female criminality and subversion in early modern Ireland / Andrea Knox -- Foucault 'Redux'? : the roles of humanism, protestantism, and an urban elite in creating the London Bridewell, 1500-1560 / Lee Beier -- Blackmail as a crime of sexual indiscretion in eighteenth-century England / Antony Simpson -- Henry Mayhew and the criminal classes of Victorian England : the case reopened / David Englander -- Consolidation of the Raj : notes from a police station in British India, 1865-1928 / Arvind Verma -- The White slave trade and the British Empire / Philippa Levine -- Book review essay : New directions in the history of crime and the law in early modern England / by Malcolm Gaskill -- Book reviews